2013
DOI: 10.1123/tsp.27.4.338
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Athletic Identity and Passion in Predicting Burnout in Adolescent Female Athletes

Abstract: The primary purpose of this study was to determine whether adolescent athletes' levels of sport burnout would be correlated with, or predicted by, their level and type of passion and the degree to which they identify with the athlete role. Measures for burnout, passion and athletic identity were completed by 218 high school female athletes attending summer camps. Two significant canonical functions explained the relationship of the variables. In the first canonical function, high levels of harmonious passion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 100 publications
1
54
0
6
Order By: Relevance
“…While harmonious passion typically predicts adaptive outcomes (e.g., vitality, life satisfaction), some studies have failed to substantiate these effects (e.g., Mageau et al 2005;Stenseng et al 2011). Moreover, in contrast to the dualistic model, there have been instances in which harmonious passion has had small positive correlations with maladaptive outcomes (e.g., negative affect, exercise dependence; Akehurst and Oliver 2014;Martin and Horn 2013). Equivocal findings have also been documented for obsessive passion.…”
Section: Moderation Of the Passion-outcome Relationshipsmentioning
confidence: 82%
“…While harmonious passion typically predicts adaptive outcomes (e.g., vitality, life satisfaction), some studies have failed to substantiate these effects (e.g., Mageau et al 2005;Stenseng et al 2011). Moreover, in contrast to the dualistic model, there have been instances in which harmonious passion has had small positive correlations with maladaptive outcomes (e.g., negative affect, exercise dependence; Akehurst and Oliver 2014;Martin and Horn 2013). Equivocal findings have also been documented for obsessive passion.…”
Section: Moderation Of the Passion-outcome Relationshipsmentioning
confidence: 82%
“…Contributing to the formulation of an athletic identity were a number of behavioral and social factors. According to Martin (2011), the strength of an individual's athletic identity is largely determined by past and current athletic experiences, as well as relative successes and failures within the athletic domain. In addition, researchers have found that student-athletes with strong athletic identity were more likely to spend a significant amount of their time with coaches, teammates, and other peer athletes, further strengthening their athletic identity (Horton & Mack, 2000).…”
Section: Athletic Identitymentioning
confidence: 99%
“…For one mixed methods article, the full text was not available. The aim of quantitative studies has been to examine the association between the strength of athletic identity and other variables including adaptation to athletic retirement (e.g., Alfermann, Stambulova, & Zemaityte, 2004), career maturity (e.g., Murphy, Petitpas, & Brewer, 1996), career decision making (e.g., Brown, Glastetter-Fender, & Shelton, 2000), burnout (e.g., E. M. Martin & Horn, 2013), eating disorders (e.g., Voelker, Gould, & Reel, 2014), attitudes towards growing old (e.g., Phoenix, Faulkner, & Sparkes, 2005), drinking behaviors (e.g., Grossbard et al, 2009), injury (e.g., Brewer, Cornelius, Stephan, & Van Athletic retirement Inductive analysis of content and meaning (Patton, 1990;Strauss, 1987;Strauss & Corbin, 1990;Taylor & Bogdan, 1984) In-depth interviews Gearing (1999) Athletic retirement Narrative analysis Biographical interviews Munroe, Albinson, & Hall (1999) The effects of non-selection Abstract and full text N/A Wheeler et al (1999) Athletic retirement in disability sport…”
Section: Interviewsmentioning
confidence: 99%